Pharmacological Strategies To Reduce ChemotherapyInduced Gastrointestinal Toxicity (Texas Journal of Medical Science, 2025)
Chemotherapy induced gastrointestinal dysfunction is a common occurrence associated with many different classes of chemotherapeutic agents. Gastrointestinal toxicity includes mucositis, diarrhea, and constipation, and can often be a dose-limiting complication, induce cessation of treatment and could be life threatening. Modulating the gut microbiome to alleviate chemotherapy-induced gastrointestinal toxicities by combining antibiotics with patient-specific probiotics/fecal microbiota transplants to target pathogenic bacteria and replenish the commensal microbiome remains an exciting prospect. In this review, we discuss our current understanding of the mechanisms underlying chemotherapy-induced diarrhea and mucositis, and emerging mechanisms involving the enteric nervous system, smooth muscle cells and enteric immune cells